Dystrophin-glycoproteins associated in congenital muscular dystrophy: immunohistochemical analysis of 59 Brazilian cases Complexo distrofina-glicoproteínas associadas na distrofia muscular congênita: análise imuno-histoquímica em 59 casos - Lucio Gobbo Ferreira; Suely Kazue Marie; Enna Cristina Liu; Maria Bernadete Dutra Resende; Mary Souza Carvalho; Milberto Scaff; Umbertina Conti Reed (Arquivos de Neuro-Psiquiatria)
The congenital muscular dystrophies (CMD) are heterogeneous muscular diseases with early and dystrophic pattern on muscle biopsy. Many different subtypes have been genetically identified and most phenotypes not yet identified belong to the merosin-positive (MP) CMD subgroup. OBJECTIVE: To analyze the immunohistochemical expression of the main proteins of the dystrophin-glycoproteins associated complex in muscle biopsy of patients with different CMD phenotypes, for investigating a possible correlation with clinical and histopathological data. METHOD: Fifty-nine patients with CMD had clinical, histopathological and immunohistochemical data evaluated: 32 had MP-CMD, 23 CMD with merosin deficiency (MD-CMD), one Ullrich phenotype and three Walker-Warburg disease. RESULTS: Dystrophin and dysferlin were normal in all; among the patients with MD-CMD, merosin deficiency was partial in nine who showed the same clinical severity as those with total deficiency; the reduced expression of a-sarcoglycan (SG) and alpha-dystroglycan (DG) showed statistically significant correlation with severe MD-CMD phenotype. CONCLUSION: There is a greater relationship between merosin and the former proteins; among MP-CMD patients, no remarkable immunohistochemical/phenotypical correlations were found, although the reduced expression of beta-DG had showed statistically significant correlation with severe phenotype and marked fibrosis on muscular biopsy. A distrofia muscular congênita (DMC) é doença muscular heterogênea, de início precoce e padrão histopatológico de distrofia. Diversos subtipos foram geneticamente identificados e os fenótipos ainda não identificados pertencem em geral ao subgrupo de DMC merosina-positiva (MP). OBJETIVO: Analisar a expressão imuno-histoquímica das principais proteínas do complexo distrofina-glicoproteínas associadas na biópsia muscular de pacientes com diferentes fenótipos de DMC, a fim de investigar uma eventual correlação com o quadro clínico e histopatológico. MÉTODO: Cinqüenta e nove pacientes com DMC foram avaliados clinicamente e sua biópsia muscular, histopatologica e imuno-histoquimicamente: 32 eram MP, 23 merosina-deficiente (MD), um mostrava fenótipo Ullrich e três síndrome de Walker-Warburg. RESULTADOS: Distrofina e disferlina foram normais em todos; nove pacientes MD apresentavam déficit parcial de merosina, porém com a mesma gravidade clínica daqueles com deficiência total. CONCLUSÃO: A hipoexpressão de a-sarcoglicana (SG) and alfa-distroglycan (DG) se correlacionou estatisticamente com o grave fenótipo MD, assim indicando maior correlação entre a merosina e as referidas proteínas; entre os pacientes MP, apesar da hipoexpressão de beta-DG ter se correlacionado significativamente com fenótipo e histopatologia mais grave, não houve correlação clínica/imuno-histoquímica valorizável.